COSTS AND RETURN OF FARO-44 RICE FARMERS’ BENEFICIARIES OF THE FADAMA III ADDITIONAL FINANCE II IN TARABA STATE, NIGERIA - Banseka, R. F.; Sani, M. H.; Sani, R. M.; Murtala, N. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study was carried out to analyse the costs and return of faro-44 rice farmers’ beneficiaries of the fadama III additional finance II in Taraba State, Nigeria. Multi-stage sampling procedure was used to select the 500 respondents. Data were analyzed using descriptive statistics (mean, percentages and tables) and inferential statistics (farm budget techniques or cost-benefit analysis). The findings showed that in wet cropping season, average labour cost of ploughing and harrowing was N23,600.23 (11.84%) with t-value of 7.1268 and significant at P≤0.01. In dry and wet cropping season, cost of land clearing was N32,500.33 (13.18%) and N17,500.00 (8.78%) with t-value of 3.4534 significant at P≤0.01. Cost of planting, harvesting, threshing, winnowing, bagging and were significant at P≤0.01 with their corresponding t-values of 3.5407; 5.9132; 4.4771; 3.5463 and 5.4935, respectively. In dry season, the respondents realized N1,569,780.00 as total revenue from 6,156 kg of paddy rice produced compared to N696,795.00 as total revenue in wet season. Similarly, sale of rice straws yielded total value of N108,800.00 in dry season compared to N29,200.00 in wet season. The respondents consumed 372 bags more rice in wet season valued at N61,380.00 compared to 164 bags in dry season valued at N41,820.00. The results further disclosed that dry season faro-44 rice farmers incurred total cost of N304,738.91 compared to wet season total cost of N225,840.33. Realizable revenue of N1,720,400.00 in dry season and N787,375.00 in wet season with net farm income of N1,415,661.09 and N561,534.67 in dry and wet seasons, respectively. With profit index of 5.74 and 2.82 in dry and wet seasons, respectively, the faro-44 rice farmers realized more profits in dry season as it is also glaring from the rate of returns on investment (RRI) of 4.65 (dry season) and 2.49 RRI in wet season. These results indicated that faro-44 rice farming is profitable in Taraba State meaning that for every N1 invested in faro-44 rice production, the farmers realized N4.65 and N2.49 in dry and wet seasons, respectively. The study concluded that faro-44 rice productivity is profitable in Taraba State; and that ploughing and harrowing was major on-farm rice activity carried out in wet season while land clearing was majorly an activity of dry season. It was recommended that faro-44 rice farmers in Taraba State should be given more cash-for-work supports; advisory services; supports for non-farm activities and capacity building on agribusiness, enterprise of farmers’ choice, record keeping.